148k views
1 vote
Solve the system with
elimination.
2x - y = 3
9x – 6y = 6

User Sergio
by
7.9k points

1 Answer

4 votes

Answer: x = 4, y = 5

Explanation:

To solve by elimination, we must first eliminate one of the variables of the equations. We'll get rid of y, and to do this, you have to multiply 2x - y = 3 by -6.

-6(2x - 7 = 3)

-12x + 6 = -18

Now add -12x + 6 = -18 to with 9x - 6y = 6 to get rid of y.

-3x = -12 Solve for x

x = 4

Now plug x back into the original equation to solve for y.

2(4) - y = 3

8 - y = 3

-y = -5

y = 5

Your final solution is (4, 5)

User Nick Legend
by
7.0k points